2012
DOI: 10.1097/ss.0b013e318239398b
|View full text |Cite
|
Sign up to set email alerts
|

Poultry Manure Application Time Impact on Corn Grain Production in a Crider Silt Loam

Abstract: Adopting proper management practices for poultry litter (PL) is critical to increase N efficiency, maximize yield, and reduce negative environmental impacts. This study investigated the effects of application time (fall and spring) of two PL rates (9.0 and 18.0 Mg ha j1 ) and commercial N-P-K fertilizer blend (224 kg N ha j1 , 84 kg P ha j1 , 145.6 kg K ha j1 ) on selected soil properties and corn (Zea mays L.) grain yield in Central Kentucky. Application time response was measured by grain yield, whole plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…This likely is because the organic form of litter N has to undergo mineralization before it is subject to loss. But the reduction of about 15% grain and biomass yield if the litter is applied in the fall is substantial considering fall‐applied litter in colder regions does not lead to yield reduction (Jn‐Baptiste et al, 2012; Ruiz Diaz and Sawyer, 2008). Overall, our results suggest up to 15% grain yield reduction should be expected if poultry litter is applied in the fall in regions with similar environments as that of northern Mississippi with an added risk of adverse environmental effects which have not been determined in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This likely is because the organic form of litter N has to undergo mineralization before it is subject to loss. But the reduction of about 15% grain and biomass yield if the litter is applied in the fall is substantial considering fall‐applied litter in colder regions does not lead to yield reduction (Jn‐Baptiste et al, 2012; Ruiz Diaz and Sawyer, 2008). Overall, our results suggest up to 15% grain yield reduction should be expected if poultry litter is applied in the fall in regions with similar environments as that of northern Mississippi with an added risk of adverse environmental effects which have not been determined in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In Iowa, Ruiz Diaz and Sawyer (2008) reported that corn fertilized with fall‐ or winter‐applied chicken ( Gallus gallus ) and turkey ( Meleagris gallopavo ) manure produced equal grain yield as corn fertilized with spring‐applied manure. Similarly, in Kentucky, Jn‐Baptiste et al (2012) reported that the grain yield of corn fertilized with poultry litter was not affected whether the litter was applied in the fall or spring.…”
mentioning
confidence: 97%
“…The warmer fall and winter Alabama temperatures are conducive for rapid mineralization of organic matter from the PL. This is unlike locations such as Iowa, where soil temperatures are usually below 10-C during fall and winter, and even milder temperatures such as Kentucky, which allow for reduced nitrification and N losses (Killorn and Lorimor, 2003;Kyveryga et al, 2004;Jn-Baptiste et al, 2012). In addition, greater NO 3 -N losses occur through leaching from longer periods of nitrification before plant uptake (Randall and Vetsch, 2005).…”
Section: Corn Grain Yieldmentioning
confidence: 92%
“…More so, planting time becomes critical because of wet springs, which allow small windows of opportunity for planting and is less favorable for land preparation (Ruiz Diaz and Sawyer, 2008;Randall et al, 2003). Fall application was as effective as in spring on corn grain yield in regions with cold winters, such as Iowa (Ruiz Dias and Sawyer, 2008), and even regions with milder winters, such as Kentucky (Jn-Baptiste et al, 2012); however, in warmer regions such as northern Mississippi, significantly lower corn grain yield was obtained from fall than spring-applied PL (Tewolde and Sistani, 2010). Documentation of research for PL application timing on corn in northern Alabama is limited or absent altogether.…”
mentioning
confidence: 97%
“…However, the production of chemical fertilizers needs to use non-renewable resources and is an energy consumption process. To achieve sustainable development of agriculture, the nutrients in livestock manure need to be recycled and reused to meet the need of fertilizers for Sustainability 2018, 10, 2536 2 of 17 crop production [4,5]; at the same time, methods of properly managing livestock manure need to be developed to avoid potential problems such as the emissions of odorous gases to local residential areas [6], and the release of heavy metals in livestock manure to the environment.…”
Section: Introductionmentioning
confidence: 99%